IMPLEMENTASI MENAJEMEN BERBASIS SEKOLAH (MBS) DALAM MENINGKATKAN MUTU SEKOLAH MELALUI PERAN STAKEHOLDERS DI SD NO. 3 LEGIAN - Chindytia; Anak Agung Gede Agung; Putu Putri Satiari; I Nyoman Aries Wira Saputra; Komang Randy Arjuna Sutrisna (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to analyze the implementation of School-Based Management (SBM) in improving school quality through the role of stakeholders at SD No. 3 Legian. The study employed a qualitative approach with a descriptive method. Data were collected through in-depth interviews with the school principal, direct observation, and documentation studies, and subsequently analyzed using the interactive model of Miles and Huberman. The results indicate that the implementation of SBM at SD No. 3 Legian was carried out by involving internal stakeholders, including the principal, teachers, staff, and students, as well as external stakeholders, including parents, the school committee, the Department of Education, the surrounding community, universities, and local business actors. Collaborative activities were realized through programs such as market day, environmental care, arts performances, Teacher Working Groups (KKG), and various social activities. Challenges encountered included limited operational funds, parents' time constraints due to work obligations, and limited community awareness, which were addressed through open communication and the utilization of digital technology. Stakeholder support was proven to have a positive influence on the improvement of academic quality, non-academic quality, and public trust in the school. Transparency and accountability in school management fostered a sustainable cycle of participation, resulting in continuous improvement of educational quality at SD No. 3 Legian. Keywords: School-Based Management (SBM), educational quality, stakeholders, implementation, elementary school